METODE DIFERENSIASI DALAM PELAJARAN WACANA BERBAHASA BALI KURIKULUM MERDEKA KELAS X DI SMA DHARMA PRAJA DENPASAR - Utari, Ni Putu Christina Bintang (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
SMA Dharma Praja Denpasar has recently implemented the Independent Curriculum, using the differentiation method in Balinese language learning. Tomlinson (2001) defines differentiated learning as adapting classroom processes to meet individual student needs. This research examines three key areas: (1) how the differentiation method is implemented; (2) challenges and efforts made by teachers; (3) the impact of this method. Theories used include behaviorism and constructivism. Data was collected through observation, interviews, literature, and documents, and analyzed using data reduction, presentation, and conclusion methods. The findings are: (1) Teachers implement differentiation by grouping students based on their learning styles (visual, auditory, kinesthetic); (2) Challenges include limited teacher knowledge, time constraints, and the perception of Balinese as a foreign language. Teachers address these by self-studying, providing extra time for students, and frequently using the method. (3) The differentiation method positively impacts student engagement, enthusiasm, and motivation.